The effect of the colostral cells on gene expression of cytokines in cord blood cells - Hrdý, Jiří; Novotná, Olga; Kocourková, Ingrid; Prokešová, Ludmila (Folia microbiologica, 2017)
Beneficial effect of maternal milk is acknowledged, but there is still question whether maternal milk from allergic mother is as good as from healthy one. In our study, we have assayed the effect of cells from colostrum of healthy and allergic mothers on gene expression of cytokines in cord blood cells of newborns of healthy and allergic mothers. Cytokines typical for Th1 (IL-2, IFN-gamma), Th2 (IL-4, IL-13), Tregs (IL-10, TGF-beta), and IL-8 were followed. We were not able to detect significant influence of colostral cells on gene expression of cytokines in cord blood after 2-day coculture using Transwell system. There was no difference in gene expression of cytokines in nonstimulated cord blood cells of newborns of healthy and allergic mothers, but generally increased gene expression of cytokines except IL-10 and TGF-beta after polyclonal stimulation was detected in cord blood cells of children of allergic mothers. There was no difference in IL-10 expression in stimulated cord blood cells of children of healthy and allergic mothers. Gene expression of TGF-beta was even decreased in stimulated cord blood cells of children of allergic mothers in comparison to healthy ones. We have not observed difference in the capacity of colostral cells of healthy and allergic mothers to influence gene expression of cytokines in cord blood cells, but we have described difference in the reactivity of cord blood cells between children of allergic and healthy mothers.
Keywords: Increase Gene Expression; Cord Blood Sample; novorozenec; Th1 buňky; Infant, Newborn; exprese genu; Infant; Humans; Pregnancy; Gene Expression; kojenec; alergie; Th2 buňky; cytokiny; Female; mladý dospělý; dospělí; interleukin-13; Colostrum; Interleukin-10; Hypersensitivity; lidé; Cord Blood Cell; Regulatory Cytokine; Fetal Blood; Adult; Interleukin-4; kolostrum; ženské pohlaví; fetální krev; Male; Th2 Cells; těhotenství; Cytokines; Th1 Cells; interleukin-4; Young Adult; interleukin-10; mužské pohlaví; Interleukin-13; Cord Blood